Pengembangan Produk Fashion Berbasis Batik: Vest Modern Dengan Kualitas Premiun (Motifara) - Arumsari; Kurnia Octaviani, Saly; Artha Putra Illahi, Dewanatan (Redtech Putra Benua, 2025)
Batik, as one of Indonesia's cultural heritages, faces significant challenges in the modern era, particularly in attracting interest from younger generations. Many young people perceive batik as outdated and incompatible with current fashion trends. To address this issue, a community service team from Universitas Tiga Serangkai developed a modern batik-based fashion product in the form of a premium vest called MOTIFARA. This program was conducted in collaboration with the Batik Arkanza SME in Laweyan, Surakarta. The methods used included customer interviews, direct observation, and product development through market surveys and prototype evaluations. The resulting vest utilized high-quality primisima cotton fabric, featuring simple motifs and neutral colors tailored to the preferences of young consumers. The program's outcomes indicate that innovative designs rooted in local cultural values can significantly enhance the appeal of batik among younger generations and support cultural preservation through fashion media. The MOTIFARA vest is expected to serve as a model for culturally rich yet modern fashion products that are competitive in today’s fashion market.